2022
DOI: 10.1101/2022.11.02.514909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human FcγRIIIa activation on splenic macrophages drives the in vivo pathogenesis of dengue disease

Abstract: Although dengue virus (DENV) infection typically causes asymptomatic disease, DENV-infected patients can experience severe complications. A risk factor for symptomatic disease is pre-existing anti-DENV IgG antibodies. Cellular assays suggested that these antibodies can enhance viral infection of Fcγ receptor (FcγR)-expressing myeloid cells. Recent studies, however, revealed more complex interactions between anti-DENV antibodies and specific FcγRs by demonstrating that modulation of the IgG Fc glycan correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Using in vitro monocytic cell line, afucosylated DENV immune complexes engaged FcγRIIIa to increase immunoreceptor tyrosine-based afucosylated IgG motif (ITAM) signalling that enhanced infection [ 35 ]. In vivo studies revealed that afucosylated IgG1–FcγRIIIa interacts with splenic macrophages that promoted viral replication and anti-afucosylated IgG1 nanobodies protected against ADE pathogenicity in mice [ 36 , 37 ]. In SARS-CoV-2 infection, the uptake of afucosylated immune complexes by mononuclear cells was shown to trigger pro-inflammatory cytokine production such as TNF, IL-1β, and IL-6 [ 23 ].…”
Section: Potential Pathways Triggered By Afucosylated Igg1s In Denguementioning
confidence: 99%
“…Using in vitro monocytic cell line, afucosylated DENV immune complexes engaged FcγRIIIa to increase immunoreceptor tyrosine-based afucosylated IgG motif (ITAM) signalling that enhanced infection [ 35 ]. In vivo studies revealed that afucosylated IgG1–FcγRIIIa interacts with splenic macrophages that promoted viral replication and anti-afucosylated IgG1 nanobodies protected against ADE pathogenicity in mice [ 36 , 37 ]. In SARS-CoV-2 infection, the uptake of afucosylated immune complexes by mononuclear cells was shown to trigger pro-inflammatory cytokine production such as TNF, IL-1β, and IL-6 [ 23 ].…”
Section: Potential Pathways Triggered By Afucosylated Igg1s In Denguementioning
confidence: 99%
“…One recent study from our laboratory generated a novel mouse model of ADE that is both permissive to DENV infection and recapitulates human Fc-FcγR interactions in vivo (49) . This study identified afucosylated IgG1-FcγRIIIa interactions as the chief determinant of ADE severity.…”
Section: Resultsmentioning
confidence: 99%
“…S1A, Table 1). The loop architecture of the crystal structure for CDR1 (residues 26-34) and CDR2 (residues [46][47][48][49][50][51][52][53][54][55][56][57][58] aligned very closely with its predicted structure, however, electron density for CDR3 (residues 91-108) deviated considerably and packed closer to the globular Ig fold of the nanobody than predicted. Consistent with the previously mentioned characteristics of camelid nanobodies, the CDR3 loop protruded considerably from the main body of the molecule, indicating its inherent flexibility and potential to reach recessed epitopes, such as the N-glycans buried in the cleft of IgG molecule (33).…”
Section: Crystal Structure Of the Afucosylated Igg-specific Nanobody X0mentioning
confidence: 86%